Pengaruh Motivasi, Komunikasi, Dan Stres Kerja Terhadap Kepuasan Kerja Karyawan PT. Toeng Market Surabaya - Damayanti, Alvina Putri; Pardiman, Pardiman; Rahmawati, Rahmawati (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This Research Aims To Test And Explain The Influence Of Motivation, Communication And Work Stress On Job Satisfaction Of Employees. Toeng Market Company Surabaya. This Research Uses A Quantitative Approach Where The Number Of Samples Is 82. To Solve Problem In This Research Using Spss Assistance In Analyzing Various Type Of Tests, Carried Out Such As Validity Tests, Reability Test, Test Normality, Classical Assumption Test, Hypothesis Test, Multiple Liniear Regression Test And Test Coefficient Of Determination Adjusted R2. The Results Of This Research Are That Motivation, Communication And Work Stres Have A Simultaneous Effect On Job Satisfaction, And Motivation And Communication Partially Have A Positive Effect On Job Satisfaction, While Work Stres Has A Negative Effect On Job Satisfaction. Keywords : Motivation, Communication, Job Stress, Job Satisfaction.